2008
DOI: 10.1038/ejhg.2008.23
|View full text |Cite
|
Sign up to set email alerts
|

ABCA4 gene analysis in patients with autosomal recessive cone and cone rod dystrophies

Abstract: The ATP-binding cassette (ABC) transporters constitute a family of large membrane proteins, which transport a variety of substrates across membranes. The ABCA4 protein is expressed in photoreceptors and possibly functions as a transporter for N-retinylidene-phosphatidylethanolamine (N-retinylidene-PE), the Schiff base adduct of all-trans-retinal with PE. Mutations in the ABCA4 gene have been initially associated with autosomal recessive Stargardt disease. Subsequent studies have shown that mutations in ABCA4 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 30 publications
0
27
0
5
Order By: Relevance
“…The c.5461-10T4C variant was found to be the most prevalent allele among patients with autosomal recessive cone and cone-rod dystrophy (8 of 64 patients). 34 In another study, the variant was found in 27 of 518 STGD1 patients compared with 1 of 316 clinically matched control individuals. 33 It is to be noticed that another affected member (VI:10) in the same family was homozygous for the c.5461-10T4C mutation.…”
Section: Discussionmentioning
confidence: 94%
“…The c.5461-10T4C variant was found to be the most prevalent allele among patients with autosomal recessive cone and cone-rod dystrophy (8 of 64 patients). 34 In another study, the variant was found in 27 of 518 STGD1 patients compared with 1 of 316 clinically matched control individuals. 33 It is to be noticed that another affected member (VI:10) in the same family was homozygous for the c.5461-10T4C mutation.…”
Section: Discussionmentioning
confidence: 94%
“…Cependant, les résultats du bilan électrophysiologique pratiqué ne permettent pas de trancher absolument entre une dystrophie des cônes et une maladie de Stargardt, tant ces pathologies ont de points communs (Kitiratschky, Grau, Bernd, Zrenner, Jagle, Renner, Kellner, Rudolph, Jacobson, Cideciyan, Schaich, Kohl & Wissinger, 2008), (Shastry, 2008).…”
Section: Difficultés Diagnostiquesunclassified
“…Ce résultat ne permet pas non plus d'étiqueter de façon absolue la pathologie en cours ; en effet, il a été montré que la dystrophie des cônes ou la cone-rod dystrophy présentaient dans 30% des cas, des mutations du gène ABCA4 (Kitiratschky et al, 2008)… L'évolution tranchera… L'évolution fonctionnelle déterminera si l'épithélium pigmentaire et les bâtonnets sont secondairement davantage impliqués (voir exemple de l'évolution d'une maladie de Stargardt au chapitre VI-1) ou si le dysfonctionnement constaté reste limité aux cônes maculaires.…”
Section: Résultat Génétiqueunclassified
“…Une mutation du gène ABCA4 n'est pas pathognomonique de la maladie de Stargardt et se retrouve dans des pathologies avec atteinte maculaire comme la dystrophie des cônes ou les cone-rod dystrophies [Kitiratschky et al, 2008]. Les erreurs ou errances de diagnostic sont donc compréhensibles.…”
Section: Absence De Relation : Résultats Fonctionnels/phénotypes/génounclassified